Enhancing Academic Writing ability for Higher Education Students - Reflinda Reflinda (VISION, 2016)
Becoming higher education students is quite different from Senior High School Students. Higher education students are demanded to develop their study skills such as managing own self, managing time, reading efficiency, and develop academic writing. This paper aims to discuss how to improve writing skill especially academic writing that is always faced by students in higher education. In writing academic essays there are three main activities for academic writing, first, writing foundation, second, reading and note taking and third, writing stage.Keywords: enhancing, academic writing, higher Education students